The Awareness of Special Education Teachers about Comprehensive Sexuality Education - Çimen Oğur; Seray Olçay (e-Kafkas Eğitim Araştırmaları Dergisi, 2024)
Comprehensive sexuality education aims to equip individuals with relevant knowledge, skills, attitudes and values, assist them in the establishment of adequate social and sexual relationships, and maximize their awareness about decision-making and their rights. It was reported in the literature that individuals with autism spectrum disorder (ASD) are one of the disability groups that require sexuality education. It was emphasized that teachers play a key role in sexuality education. The present descriptive study aimed to determine the knowledge and experience levels, and professional development requirements of the teachers who instruct individuals with ASD in comprehensive sexuality education. The study was conducted with 200 volunteering teachers, and the study data were collected with a survey form. The study findings indicated that only 10% of the teachers instructed sexuality education to individuals with ASD, and the teachers did not have adequate knowledge on comprehensive sex education content. They focused on the biological dimension of comprehensive sexuality education, and they did not instruct the content associated with relationship, rights, culture, and skills that ensure the health and well-being of the individuals. The findings are discussed based on the previous studies, and practical recommendations and suggestions for further research are presented.